Quantitative histological study of mucosal inflammatory cell densities in endoscopic duodenal biopsy specimens from dyspeptic patients using computer linked image analysis. Issue 8 (August 1990) - Collins, J S; Hamilton, P W; Watt, P C; Sloan, J M; Love, A H
Abstract : Inflammatory cell counting in endoscopic biopsy sections was carried out on duodenal mucosal samples from defined sites in patients with duodenal ulcer, duodenitis but no ulcer, non-ulcer dyspepsia, and asymptomatic controls using computer linked image analysis. The variables measured included polymorphonuclear and mononuclear cells per mm of superficial epithelium and per mm2 lamina propria. Duodenal ulcer crater margin and mucosal biopsy specimens from endoscopically inflamed mucosa in the group with duodenitis but no ulcer showed significantly higher inflammatory cell counts than endoscopically normal non-ulcer dyspepsia and control mucosa. Biopsy specimens from non-ulcer dyspepsia patients showed significantly higher lamina propria polymorphs than control group mucosa. Endoscopically normal duodenal ulcer and duodenitis but no ulcer mucosa also showed significantly higher acute and chronic inflammatory cell counts than controls. The prevalence of Helicobacter pylori in duodenal biopsy specimens was low (0-22%) and unrelated to local inflammatory response. Despite histological appearances, duodenal biopsy specimens from non-ulcer dyspepsia patients showed significantly higher inflammatory cell infiltration than control specimens, suggesting that at least some represent part of a spectrum of subclinical peptic disease.